A QUANTITATIVE STRUCTURE-PROPERTY RELATIONSHIP (QSPR) EVALUATION OF CRITICAL VOLUME OF UNSATURATED HYDROCARBON ALKENES AND ALKYNES USING SIMPLE CONNECTIVITY INDICES - Oman Zuas; Dyah Styarini (Reaktor, 2009)
A quantitative structure-property relationships (QSPR) was used in this study to relate the critical volume (Vc) of unsaturated hydrocarbons alkenes and alkynes compounds to their molecular structures. A QSPR study of Vc was performed on the basis of simple connectivity indices (SCI’s). The obtained QSPR model is predictive and requires only one SCI descriptor in the calculation with statistical parameters including standard coefficient correlation (R2)=0.997, cross-validated correlation coefficients (Q2)=0.976, and average absolute error (AAE)=0.12. Application of the best QSPR model to a testing set of 30 alkenes and alkynes demonstrates good predictability without the needs in any experimental physicochemical properties data.